2017
DOI: 10.1108/jsm-07-2016-0272
|View full text |Cite
|
Sign up to set email alerts
|

Internal market orientation determinants of employee brand enactment

Abstract: Purpose This study aims to explore how the adoption of internal market orientation (IMO) can enhance front-line employee brand enactment within an interpersonal service setting. Insights from equity theory and the person – environment paradigm are drawn upon to develop a theoretical model describing the impact of IMO on employee – organization fit, employee – supervisor fit and employee – job fit and the consequences of IMO on employee brand knowledge and brand identification. Second, the role of various types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 89 publications
4
63
0
2
Order By: Relevance
“…A few researchers have tried to encompass some internal organizational phenomenon like behaviors and attitudes into MO (Avlonitis & Gounaris, 1999;Boukis, Gounaris, & Lings, 2017), while the others count into MO, some external environmental factors such as competitors and distributors as well (Javanmard & Hasani, 2017;Lado, Maydeu-Olivares, & Rivera, 1998). Sharp (2001) argues that MO must take into account the customer satisfaction as well as the product development phenomenon, whereas, Hult, Cravens, and Sheth (2001) consider MO as consisting value chain components that cover "culture-behaviors-processes-actions-performance."…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few researchers have tried to encompass some internal organizational phenomenon like behaviors and attitudes into MO (Avlonitis & Gounaris, 1999;Boukis, Gounaris, & Lings, 2017), while the others count into MO, some external environmental factors such as competitors and distributors as well (Javanmard & Hasani, 2017;Lado, Maydeu-Olivares, & Rivera, 1998). Sharp (2001) argues that MO must take into account the customer satisfaction as well as the product development phenomenon, whereas, Hult, Cravens, and Sheth (2001) consider MO as consisting value chain components that cover "culture-behaviors-processes-actions-performance."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior literature refers to this as entrepreneurial orientation. Researchers have paid considerable attention to entrepreneurial orientation over the last few years (Boukis, Gounaris, & Lings, 2017) to increase the performance of SMEs. To respond to this research question, some critical factors for the performance of SMEs have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, creating a favourable and robust employer brand (EB) becomes important (Schlager et al, 2011) as it helps in promoting positive attitudes among current employees, who are proud to work for a strong-branded organisation, as well as to attract the best new millennial talent successfully. Internal employee branding has been shown to be linked to organisations with a strong internal marketing orientation (IMO) (Boukis et al, 2017), which in turn improves employees’ fit within the service organisation and leads to higher job satisfaction (Gounaris and Boukis, 2013), ultimately contributing to enhanced customer satisfaction with the original and repeat service.…”
Section: Discussionmentioning
confidence: 99%